Defining and classifying technocrat‐led and technocratic governments. (10th April 2014) - McDonnell, Duncan; Valbruzzi, Marco
Abstract Governments led by technocrats remain a nebulous category in political science literature, with little clarity about how they differ from party governments, how many have existed and how we can differentiate between them. This article aims to provide that conceptual and empirical clarity. Having proposed an ideal type definition of 'technocratic government', it sets out three conditions for an operational definition of a 'technocrat' and, on that basis, lists the 24 technocrat‐led governments that have existed in 27 European Union (EU) democracies from the end of the Second World War until June 2013. It then classifies these according to their partisan/technocrat composition and remit. This allows for the presentation of a typology of four different types of technocrat‐led governments and the definition of 'full technocratic governments' as those which contain a majority of technocrats and – unlike caretaker governments – have the capacity to change the status quo. The article concludes that full technocratic governments remain extremely rare in EU democracies since there have been only six cases – of which three have occurred in the last decade.